Assessment of different semi-active control strategies on the performance of off-road vehicle suspension systems - Faris, Waleed Fekry; BenLahcene, Zohir; Ihsan, Sany Izan (inderscience publisher, 2010)
This paper deals with dynamics and control policies analysis of semi-active suspension systems for off-road vehicles. Three configurations of these vehicles; two-axle, three-axle and four-axle have been studied and their performances are compared. The application of several control policies of semi-active suspension system, namely skyhook; ground-hook and hybrid controls have been analysed and compared with passive systems. The results show that the hybrid control policy yields better comfort than a passive suspension, without reducing the road-holding quality or increasing the suspension displacement. The hybrid control policy is also shown to be a better compromise between comfort, road-holding and suspension displacement than the skyhook and ground-hook control policies. Skyhook control generally improves sprung mass responses while at the same time increasing unsprung mass responses. On the other hand, ground-hook control generally improves unsprung mass responses at the expense of the sprung mass responses. Results show an improvement in ride comfort and vehicle handling using four-axle over three-axle and two-axle when emphasis is placed on the response of the vehicle body acceleration, suspension and tyre deflection.